BCL11A interacts with SOX2 to control the expression of epigenetic regulators in lung squamous carcinoma - Kyren A. Lazarus (Nature Portfolio, 2018)
Amongst the non-small cell lung cancers, to date, lung squamous cell carcinoma remains the most challenging to treat. Here the authors report BCL11A as an important factor which together with SOX2 can drive lung squamous cell carcinoma development and highlight a potential novel therapeutic candidate for this devastating disease.